2021
DOI: 10.1002/acm2.13279
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in the positioning of patients receiving treatment for brain metastases and wearing surgical mask underneath thermoplastic mask during COVID‐19 crisis

Abstract: Thermoplastic masks, used along with surgical masks, enable immobilization methods to reduce the risk of infection in patients undergoing intracranial stereotactic radiosurgery and stereotactic radiotherapy (SRS/SRT) during the COVID-19 crisis.The purpose of this study was to investigate the feasibility of thermoplastic mask immobilization with a surgical mask using an ExacTrac system. Twelve patients each with brain metastases were immobilized using a thermoplastic mask and a surgical mask and only a thermopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…At present, in the other studies have also started to study the feasibility of patients wearing masks to receive different radiotherapy techniques. [13][14][15] In the literature, Ding et al 13 The CBCT was mainly used to measure the difference of patient's position when patient was treated using HN and HNS thermoplastic mask with/without Surgical Mask. Miura et al 14 mainly used ExacTrac positioning combined with IGRT evaluate the fixation of patients undergoing intracranial stereotactic radiosurgery and stereotactic radiotherapy (SRS/SRT) with/without surgical masks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the other studies have also started to study the feasibility of patients wearing masks to receive different radiotherapy techniques. [13][14][15] In the literature, Ding et al 13 The CBCT was mainly used to measure the difference of patient's position when patient was treated using HN and HNS thermoplastic mask with/without Surgical Mask. Miura et al 14 mainly used ExacTrac positioning combined with IGRT evaluate the fixation of patients undergoing intracranial stereotactic radiosurgery and stereotactic radiotherapy (SRS/SRT) with/without surgical masks.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In the literature, Ding et al 13 The CBCT was mainly used to measure the difference of patient's position when patient was treated using HN and HNS thermoplastic mask with/without Surgical Mask. Miura et al 14 mainly used ExacTrac positioning combined with IGRT evaluate the fixation of patients undergoing intracranial stereotactic radiosurgery and stereotactic radiotherapy (SRS/SRT) with/without surgical masks. Ohhira et al 15 compared the intrafractional setup error with and without a bite block during fractionated intracranial stereotactic irradiation of patients wearing medical masks.…”
Section: Discussionmentioning
confidence: 99%
“…18 The uncertainty in patient positioning with and without a surgical mask during thermoplastic immobilization has been studied. 19 EPID dosimetry can be used to compare the delivered fluence with planned fluence using advanced radiotherapy techniques. Various studies have shown that the accuracy of the measured fluence is equivalent to that of other measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties and variations exist in the positioning of SRS and stereotactic radiotherapy treatment techniques with non‐coplanar beams 18 . The uncertainty in patient positioning with and without a surgical mask during thermoplastic immobilization has been studied 19 . EPID dosimetry can be used to compare the delivered fluence with planned fluence using advanced radiotherapy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written about the impact of the pandemic on medical education, including the recruitment, 21 training, 22,23 and certification 24 of medical students and residents. The impact of COVID-19 on medical physics has been widely discussed, covering topics such as general clinical practice, 25 staffing, [26][27][28] the impact of infection control measures on treatment delivery, 29,30 and academic medicine. 31 Viscariello et al 32 investigated the potential risks associated with pandemic-related radiation oncology workflow adaptations.…”
Section: Introductionmentioning
confidence: 99%